Annual Report 2010-11 - Planning Commission (Planning Commission, 2011)
The Unique Identification Authority of India (UIDAI) has been constituted in January, 2009 as an attached office under aegis of Planning Commission. UIDAI shall have the responsibility to lay down plan and policies to implement U1D Scheme, shall own and operate UID database and be responsible for its updation and maintenance on an ongoing basis. Headquarter of UIDAI is in Delhi and it has its Regional Offices in eight places.
Government of India Planning Commission New Delhi
Planning Commission
Keywords: Housing and Urban Affairs Division; Industry Division; International Economics Divsion; Labour; Employment and Manpower Division; Multi Level Planning (MLP) Division; Plan Coordination and Management Division; Power and Energy Division; Project Appraisal and Management Division; Perspective Planning Division; Rural Development Division; Science and Technology Division